The secret of the three cities: an introduction to Hindu Śākta tantrism - Brooks, Douglas Renfrew (Univ. of Chicago Press, 1990)
501, 370 u. 380 auf Wunsch von HDUB ergänzt - keine eigene Titelseite dafür vhd.